Próba oceny szans i zagrożeń sieci NATURA 2000 w Polsce - Zielińska, Anetta (The NATURA 2000 Possibilities and Threats in Poland, 2005)
NATURA 2000 is the system of protecting selected nature elements which are the most important and the most valuable from European point of view, they actually make the network of protected spaces on UE territory.Positive parts of NATURA 2000 network are the following:- creating a coherent system of protecting the most valuable elements of the natural environment in Europe;- constant development, modernization of the network to new needs in the area of protecting biodiversity in Europe;- the acquisition of meaningful financial recourses from the European Union;- possibilities of the economic progress according to eco-development;- ecological education about the environmental protection.Negative parts of NATURA 2000 network are the following:- infficient number and space of the territory proposed by Polish government;- lack of precise analyses of the natural biotope mapping in the scale of the whole country as well as cataloguing plants and animals species;- according to the law regulation concerning nature protection of some areas, there are two different protection plans, dealing with two different protection forms (national park, NATURA 2000 area);- indirect expenses related to NATURA 2000 project;- lack of understanding of NATURA 2000 program by local community.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (3); 2005; nr 1075, s. 168-175